2015
DOI: 10.1097/scs.0000000000001416
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Distraction Osteogenesis for the Treatment of Neonatal Tongue-Based Airway Obstruction

Abstract: Early postnatal tracheostomy for airway compromise is associated with high morbidity and cost. In certain patients with tongue-base airway obstruction (TBAO), mandibular distraction osteogenesis may be preferred. We present a comprehensive analysis of surgical, airway, and cephalometric outcomes in a large series of neonatal patients with TBAO. A retrospective review was performed of patients with laryngoscopically proven TBAO who underwent mandibular distraction osteogenesis before 1 year of age at our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Regardless of the intervention, careful patient selection is necessary to anticipate potential complications and achieve optimal outcomes. In both MDO 53,60,61,77 and TLA 36,48,78 syndromic patients tended to have poorer airway and feeding outcomes. Subjects who still required gastrostomy after either MDO or TLA often had an associated syndrome 43,53,56,60 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Regardless of the intervention, careful patient selection is necessary to anticipate potential complications and achieve optimal outcomes. In both MDO 53,60,61,77 and TLA 36,48,78 syndromic patients tended to have poorer airway and feeding outcomes. Subjects who still required gastrostomy after either MDO or TLA often had an associated syndrome 43,53,56,60 .…”
Section: Discussionmentioning
confidence: 95%
“…Additional studies are required to identify risk factors for MDO perioperative complications. Of particular interest would be whether syndromic PRS subjects are more prone to perioperative complications, given that several studies have shown they have poorer feeding and airway outcomes 39,53,60,61,77 . Expanded knowledge of risk factors and continued advances in operative technique can help to reduce complications, increasing the benefit to risk ratio of MDO over TLA.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures such as mandibular distraction osteogenesis can increase the size of the retroglossal airway relative to the tongue, effectively treating OSA. 4 Similarly, in patients with Down syndrome, tongue size is one risk factor for OSA. In a study using upper airway magnetic resonance imaging (MRI), Guimaraes and colleagues showed that patients with Down syndrome had relative macroglossia compared to healthy controls.…”
Section: The Tongue As a Risk Factor For Osamentioning
confidence: 99%
“…Mandibular distraction osteogenesis (MDO) has become the first-line operation in many centers for infants with airway obstruction associated with (Pierre) Robin sequence (RS) who have failed non-invasive management 1 . This procedure boasts high rates for successful resolution of obstructive sleep apnea (OSA) and avoid-ance of tracheostomy [2][3][4][5][6][7][8][9][10][11][12] . Long-term complications associated with the position of the osteotomies, such as injury to developing teeth and the inferior alveolar nerve, however, are common 1,[13][14][15] .…”
mentioning
confidence: 99%